2009
DOI: 10.1007/s10295-009-0528-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cellulose-degrading bacteria from the deep subsurface of the Homestake gold mine, Lead, South Dakota, USA

Abstract: The present study investigated the cultivable mesophilic (37 degrees C) and thermophilic (60 degrees C) cellulose-degrading bacterial diversity in a weathered soil-like sample collected from the deep subsurface (1.5 km depth) of the Homestake gold mine in Lead, South Dakota, USA. Chemical characterization of the sample by X-ray fluorescence spectroscopy revealed a high amount of toxic heavy metals such as Cu, Cr, Pb, Ni, and Zn. Molecular community structures were determined by phylogenetic analysis of 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 43 publications
4
104
0
1
Order By: Relevance
“…The basal medium used in this study contained the following: 1.0 g/L KH2PO4, 1.145 g/L K2HPO4, 0.5 g/L MgSO4.7H2O, 5.0 g/L NH4SO4, 0.05 g/L CaCl2.2H2O, and 1 mL Nitsch's trace element solution (2.2 g MnSO4, 0.5 g ZnSO4, 0.5 g H3BO3, 0.016 g CuSO4, 0.025 g Na2MoO4, and 0.046 g CoCl2) (Rastogi et al 2009). The pH of the medium was corrected to pH 7.…”
Section: Medium Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The basal medium used in this study contained the following: 1.0 g/L KH2PO4, 1.145 g/L K2HPO4, 0.5 g/L MgSO4.7H2O, 5.0 g/L NH4SO4, 0.05 g/L CaCl2.2H2O, and 1 mL Nitsch's trace element solution (2.2 g MnSO4, 0.5 g ZnSO4, 0.5 g H3BO3, 0.016 g CuSO4, 0.025 g Na2MoO4, and 0.046 g CoCl2) (Rastogi et al 2009). The pH of the medium was corrected to pH 7.…”
Section: Medium Formulationmentioning
confidence: 99%
“…Previous report showed that thermostable cellulase from B. licheniformis JK7 (Seo et al 2013), retained only about 25% of its original activity when incubated at 80 °C for 1 h. Another Bacillus sp. isolated from deep surface of homestake gold mine exhibited a thermostable cellulase (Rastogi et al 2009); however, the enzyme completely lost its activity over 1 h incubation at 90 and 100 °C.…”
Section: Effect Of Temperature On Cellulase Stabilitymentioning
confidence: 99%
“…Several cellulose-degrading Firmicutes including, Brevibacillus, Paenibacillus, Bacillus, and Geobacillus were isolated from enrichment cultures, and isolates were found with optimum temperature for carboxymethyl cellulase (CMCase) of up to 75°C (pH 5.0). One particular isolate retained 26% CMCase activity at 60°C up to a period of 300 h (Rastogi et al, 2009). These thermostable enzymes and robust thermophilic fermentative microbes could facilitate the development of more efficient and cost-effective forms of the simultaneous saccharification and fermentation process used to convert lignocellulosic biomass into biofuels.…”
mentioning
confidence: 97%
“…Nucleotide sequence of 16S rDNA was sequenced and identified through the online BLAST program. Multiple alignment was carried out with the CLUSTALX and a neighbor-joining phylogenetic tree was reconstructed using the MEGA program version 4.0 (Rastogi et al, 2009).…”
Section: Taxonomic Studymentioning
confidence: 99%